2013
DOI: 10.1128/iai.00579-13
|View full text |Cite
|
Sign up to set email alerts
|

The p38 MAPK and JNK Pathways Protect Host Cells against Clostridium perfringens Beta-Toxin

Abstract: Clostridium perfringens beta-toxin is an important agent of necrotic enteritis and enterotoxemia. Beta-toxin is a pore-forming toxin (PFT) that causes cytotoxicity. Two mitogen-activated protein kinase ( Incubation in K؉ -free medium intensified p38 MAPK activation and cell death induced by the toxin, while incubation in K ؉ -high medium prevented those effects. While streptolysin O (SLO) reportedly activates p38 MAPK via reactive oxygen species (ROS), we showed that this pathway did not play a major role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 33 publications
2
44
0
Order By: Relevance
“…Beta-toxin induces swelling and lysis of the lymphocytic HL60 cell line, which are preceded by toxin oligomer formation (hexamer or heptamer) in membrane lipid rafts, K + efflux, and Ca ++ , Na + , and Clinfluxes [143,144]. The betadependent K + loss in HL60 was found to trigger the activation of the p38 and JNK MAPK pathways which could have a protective effect of host cell [145]. When injected intradermally, Beta-toxin induces oedema and dermonecrosis, which seem to be mediated by stimulation of sensory nerves containing tachykinins such as substance P and release of tumor [143,144].…”
Section: -Mode Of Actionmentioning
confidence: 99%
“…Beta-toxin induces swelling and lysis of the lymphocytic HL60 cell line, which are preceded by toxin oligomer formation (hexamer or heptamer) in membrane lipid rafts, K + efflux, and Ca ++ , Na + , and Clinfluxes [143,144]. The betadependent K + loss in HL60 was found to trigger the activation of the p38 and JNK MAPK pathways which could have a protective effect of host cell [145]. When injected intradermally, Beta-toxin induces oedema and dermonecrosis, which seem to be mediated by stimulation of sensory nerves containing tachykinins such as substance P and release of tumor [143,144].…”
Section: -Mode Of Actionmentioning
confidence: 99%
“…Here we show that CD31 functions as the membrane receptor for CPB, a highly potent β-PFT that plays a major role in C. perfringens type C induced fatal necro-hemorrhagic enteritis in animals and humans. Previously, it has been shown that CPB is toxic to endothelial cells, platelets and several cultured monocytic, promyelocytic, lymphoblastic and Blymphocytic cell lines (Nagahama et al, 2013;Shatursky et al, 2000;Steinthorsdottir et al, 2000;Thiel et al, 2017). Our own in vivo studies suggested that vascular endothelial cells in the small intestinal wall are the primary target for this toxin (Gurtner et al, 2010;Miclard et al, 2009a;Miclard et al, 2009b;Popescu et al, 2011;Schumacher et al, 2013).…”
Section: Discussionmentioning
confidence: 81%
“…In vitro, human and porcine endothelial cells and thrombocytes are highly sensitive to CPB (Gurtner et al, 2010;Popescu et al, 2011;Thiel et al, 2017). Other cells with reported in vitro sensitivity to CPB are monocytic, lymphoblastic and lymphocytic cell lines, however the biological role of targeting similar cells in vivo has not been elucidated yet (Nagahama et al, 2003;Nagahama et al, 2013). Intestinal and many other epithelial as well as mesenchymal cells are insensitive to CPB (Gurtner et al, 2010;Manich et al, 2008;Nagahama et al, 2003;Popescu et al, 2011;Roos et al, 2015;Shatursky et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…P38 mitogen-activated protein kinase (MAPK) is an important factor in host defense against diverse bacterial pore-forming toxins ( 17 19 ) and is activated in a pneumolysin-dependent manner in both epithelial cells ( 20 ) and macrophages ( 21 ). To investigate whether p38 MAPK detection of pneumolysin affects cytosolic access, we treated BMMs with SB203580, an inhibitor of p38 MAPK activation (MAPKi), before infection with S. pneumoniae and subcellular fractionation.…”
Section: Resultsmentioning
confidence: 99%